FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA SERVISITIS PADA WANITA DI LINGKUNGAN KELUARGA PEGAWAI NEGERI SIPIL PEMERINTAH PROVINSI KALIMANTAN BARAT - Abrori, Abrori; Hermawan, Andri Dwi; Inayati, Sri (Unnes Journal of Public Health, 2016)
the  incidence  of cervicitis have not the exact figure to explained. There is a high risk for women affected by the servisitis of disease because they do not know the factors. Theoretically, servisitis of disease caused: the cleanliness of the vulva hygien, some kinds of bacteria, cervical laceration, sexual activity, and vaginal douching. The cervicitis was one of the problems of Sexually Transmitted disease (STI), Servicitie  that less well known in the wider community. The purpose of this study was to determine the factors associated with cervicitis in women’s family environment the Civil Service of West Kalimantan Government.This is a method of observational analytic study using cross sectional. The results of this results are: there is a significant correlation between (1) vaginal douching and cervicitis (p = 0,000); (2) the cleanliness of the reproductive organs and cervicitis, (p = 0,000); (3) the cleanliness of clothing and cervicitis, (p = 0,000); (4) parity and the occurrence of cervicitis, (p = 0,000); (5) frequency of sexual intercourse and cervicitis, (p = 0,000). This study suggests that the Polyclinic of West Kalimantan Province to improve IVA service and increase laboratory germs facilities; to disseminate the impact of cervicitis and vaginal douching do counseling about the Clean and Healthy Lifestyle to maintain the cleanliness of the female reproductive organs.